Tear Trough Malar Implant Penetrating Lacrimal Sac Causing Lacrimal Obstruction and Epiphora: Case Report and Review. Issue 3 (6th December 2021) - Okafor, Linda O.; Jamison, Aaron; Ali, Syed; Malhotra, Raman
Abstract : Tear trough implantation may be associated with a number of well-reported complications. To our knowledge, penetration of the lacrimal sac has never been reported as a complication of malar or tear trough implants. We report a case of lacrimal sac penetration discovered at the time of endoscopic dacryocystorhinostomy surgery in a patient who developed epiphora soon after the tear trough implant was placed. Abstract : We present a previously unreported complication of lacrimal sac penetration causing epiphora, as a result of incorrect placement of a tear trough implant.